2016
DOI: 10.1007/s10482-016-0691-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall glycopolymers of Streptomyces albus, Streptomyces albidoflavus and Streptomyces pathocidini

Abstract: The cell wall glycopolymers of three strains of Streptomyces albus and the type strain of Streptomyces pathocidini were investigated. The structures of the glycopolymers were established using a combination of chemical and NMR spectroscopic methods. The cell wall of S. albus subsp. albus VKM Ac-35(T) was found to be comprised of three glycopolymers, viz. unsubstituted 1,5-poly(ribitol phosphate), 1,3-poly(glycerol phosphate) substituted with β-D-glucopyranose, and the major polymer, a 3-deoxy-D-glycero-D-galac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…While database mining suggests that Kdn is ancestral compared to Neu5Ac (Fig. 1; see also Files S1 and S2 in the supplemental material), current evidence of Kdn in bacteria is in pathogens of plants (which do not contain any Sia) (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…While database mining suggests that Kdn is ancestral compared to Neu5Ac (Fig. 1; see also Files S1 and S2 in the supplemental material), current evidence of Kdn in bacteria is in pathogens of plants (which do not contain any Sia) (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the first report of an O 1 ,O 6 7-membered cyclic phosphate; an O 1 ,O 3 system was previously reported for D-glucose. [31] Scheme 4. a) Possible mechanism for the formation of cyclic phosphate β-13 b) DFT energy minimised 3 CO conformation for β-13.…”
Section: Scheme 2 Phosphorylation Of Per-acetylated D-galmentioning
confidence: 99%
“…Glycosyl 1-phosphates are key intermediates in carbohydrate primary metabolism and are utilised by microorganisms to form polyphosphate architectures that constitute keys parts of their extracellular capsule and cell walls. [1][2][3][4] They serve as precursors to sugar nucleotides, [5][6] the sugar donor components utilised by glycosyltransferases in the assembly of oligosaccharides and glycans and have played a key role in the development of glycosylated natural-product-based therapeutics. [7] Additionally, glycosyl 1-phosphates have been used as substrates for glycoside phosphorylases, a rapidly expanding [8] family of CAZy enzymes for the synthesis of oligosaccharide targets [9] and also play important technological roles in the food and detergent sectors.…”
mentioning
confidence: 99%
“…Resistance to cell wall-active antibiotics is often modulated by the structure of cell wall polymers other than peptidoglycan, such as teichoic acids. We analyzed the structure of these cell wall polymers in R1-100 and revealed that they are identical to that of J1074 [9], qualitatively and quantitatively.…”
Section: Resultsmentioning
confidence: 98%